Intercellular Bridges as Protoplasmic Anastomoses between Smooth Muscle Cells - Thaemert, J. C. (The Rockefeller University Press, 1959)
In electron microscopic studies, protoplasmic anastomoses were found to occur between smooth muscle cells in the gastrointestinal tracts of rats. The protoplasmic connections are apparently cylindrical in form and contain cytoplasm having a density similar to that of the cellular regions connected. The membranes enclosing the cytoplasmic connections are continuous with the membranes of the connected cells. These connecting structures have been called intercellular bridges, which is adequately descriptive if emphasis is placed on the interpretation that they represent protoplasmic anastomoses. To emphasize this, the term may be modified; i.e., anastomotic intercellular bridges. In some cellular connections, transverse diffuse lines are seen. These may be interpreted as either disintegrating or reforming plasma membranes which is consistent with the concept that protoplasmic continuity is transitory. Since the animals were dissected under hypothermia, reduction of muscular activity by the chilling may have helped to preserve the structure of existing anastomotic intercellular bridges. The intercellular protoplasmic anastomoses may play a role in the conduction of action potentials from one smooth muscle cell to another.